Character Education Integrated Inquiry E-book: Alternative Media to Minimize Bullying of Fellow Students - Agus Ramdani; Jamaluddin; I Putu Artayasa (Jurnal Penelitian Pendidikan IPA, 2023)
At this time in the educational environment there is a lot of worrying behavior and acts of violence. One of the most frequent acts of violence is bullying behavior. Bullying often occurs caused by the character education students have. This study aims to develop an integrated inquiry e-book of character education to minimize bullying. This research is development research using a 4D development model. The technique of collecting bullying data is using a questionnaire instrument and an observation sheet. The data analysis technique used quantitative descriptive analysis. Based on the data obtained from the results of the analysis carried out, it can be concluded that the integrated inquiry e-book of character education can reduce bullying behavior in students. Most of the bullying behavior before being given treatment was in the moderate category. After being given treatment using an e-book, the perpetrator's awareness behavior can reduce/reduce intimidation. In addition, there is an increase in empathy from witnesses of bullying behavior so that it can emphasize bullying behavior. The character education integrated inquiry e-book that was developed is suitable for use in science learning and can reduce bullying among students. This is because the e-book has been facilitated with character education and actions that should not be done by students